Digital Cities. - Alizadeh, Tooran; Iveson, Kurt (Palgrave Macmillan, 2020)
This chapter focuses on the relatively new concept of ‘digital cities’, which has attracted an unprecedented level of attraction in the last decade. Unfolding the popularity of digital city practices and promises, the chapter starts with a discussion of ongoing attempts to plan for digital cities. Then, building on the notion of equality in digital city debates, the chapter discusses issues of access to the telecommunication infrastructure that is the backbone of digital cities. The chapter concludes by pointing out some of the hidden environmental and social costs of digital city practices worldwide.
Keywords: Digitalisierung; Stadtplanung; Infrastrukturausstattung; Kommunikationstechnologie; Vernetzung; Smart City